Potato-legume intercropping enhances climate resilience and adaptive capacity of smallholder farmers. Research Brief 03. - Nyawade, S.; Vandamme, Elke; Friedmann, M.; Parker, M. (International Potato Center, 2020)
In this brief, we report two potential roles of potato-legume intercropping: (i) improved control of soil erosion to make potato production more sustainable in the highlands; and (ii) optimizing soil temperatures, soil water contents and soil nutrient balance thus enabling potato production in the drier midland agro-food systems. The results are derived from six separate studies conducted between the 2014 wet season and 2018 dry season in Kenya